Urban agriculture — A necessary pathway towards urban resilience and global sustainability? - Langemeyer, Johannes; Madrid-Lopez, Cristina; Mendoza Beltran, Angelica; Villalba Mendez, Gara (Landscape and urban planning, 2021)
•Urban agriculture to deserve stronger consideration in land-use planning.•Urban agriculture enhances urban resilience, sustainability and multifunctionality.•Social and ecological vulnerabilities of and in cities are underestimated.•Global teleconnections of agricultural imports are disregarded in land-use planning.•Accounting for multifunctionality still requires stronger efforts. The Covid-19 pandemic newly brings food resilience in cities to our attention and the need to question the desired degree of food self-sufficiency through urban agriculture. While these questions are by no means new and periodically entering the global research focus and policy discussions during periods of crises — the last time during the global financial crisis and resulting food price increases in 2008 — urban and peri-urban agriculture continue to be replaced by land-uses rendering higher market values (e.g. housing, transport, leisure). The loss of priority for urban agriculture in urban land-use planning is a global trend with only a few exceptions. We argue in this essay that this development has widely taken place due to three blind spots in urban planning. First, the limited consideration of social and ecological vulnerabilities and risk-related inequalities of urban inhabitants, food shortage among them, in the face of different scenarios of global change, including climate change or pandemic events such as Covid-19. Second, the disregard of the intensified negative environmental (and related social) externalities caused by distant agricultural production, as well as lacking consideration of nutrient re-cycling potentials in cities (e.g. from wastewater) to replace emission intensive mineral fertilizer use. Third, the lack of accounting for the multifunctionality of urban agriculture and the multiple benefits it provides beyond the provision of food, including social benefits and insurance values, for instance the maintenance of cultural heritage and agro-biodiversity. Along these lines, we argue that existing and new knowledge about urban risks and vulnerabilities, the spatially explicit urban metabolism (e.g. energy, water, nutrients), as well as ecosystem services need to be stronger and jointly considered in land-use decision-making.